Mini Electrode Based on Chitosan-Activated Carbon Membrane for Detection of Paracetamol in Herbal Medicine - Ani Mulyasuryani; Rachmat Triandi Tjahjanto; Zainul Abidin (The Journal of Pure and Applied Chemistry Research, 2022)
A tube type mini electrode has been made to detect paracetamol levels in herbal medicine, the electrode is made of a glass tube with a diameter of 0.7 cm, a length of 3 cm. As the membrane is a mixture of chitosan, activated carbon from rice husk, and cetyl trimethyl ammonium (CTA)-paracetamol. The internal solution is a standard solution of 0.01 M paracetamol in a solution of phosphoric acid pH 2. The average sensitivity of the paracetamol sensor is (22.60 ± 0.01) mV/decade in a linear concentration range of 10-6 – 5x10-3 M, with an average recovery of (90.6 ± 0.5) %. Paracetamol sensor electrodes can be applied to samples of herbal medicine on the market, with an average error of (9.4 ± 0.1) %.